Implementasi pendidikan karakter berbasis kearifan lokal - Aiman Faiz; Bukhori Soleh (JINoP (Jurnal Inovasi Pembelajaran), 2021)
The integration of local wisdom, such as batik and glass painting, and other Cirebon culture in general courses (Mata Kuliah Umum/ MKU) may be an interesting alternative learning approach. This research aims to describe the implementation of character education models based on local cultural wisdom such as the ability to design batik, glass paintings, and the introduction of other typical Cirebon cultures in MKU. It employed a descriptive qualitative approach to explore naturally visible phenomena. The subjects of this research were 7th semester students of Primary School Teacher Education (Pendidikan Guru Sekolah Dasar/ PGSD), University of Muhammadiyah Cirebon (UMC), class of 2016. The data were obtained from observations and interviews involving 15 respondents consisting of students, lecturers, and the Head of PGSD UMC. The results showed that MKU increased students' knowledge and skills outside the field of education as the students were enthusiastically embraced the Cirebon culture given in MKU. It can be concluded that MKU based on local wisdom was able to hone the skills of PGSD UMC students in improving their affective, psychomotor, and cognitive abilities. Thus, students were prepared to have holistic abilities that are compatible with the challenges of a new life.